Reinventing Corporate Strategy A Case Study of Malaysia, Airlines - Jain, Kamal K .; Saeed, Mohammad (Gyan Management Journal, 2007)
This paper examines the nature and unique features of airline industry by providing insights into its structure, competitive framework and related elements. Mala_11 sia Airlines has been picked up as a case in point to understand the dimensions of airline industry. The paper examines the corporate strategy of the Malaysia_ Airlines. In this competitive environment where many airlines have not been able· to survive, Malaysia Airlines has been successful in sustaining and growing by constantly reinventing its corporate strategy.
Keywords: Corporate Strategy; Malaysia, Airlines; structure; competitive framework